Strategi Bisnis Inovatif: Kunci Kesuksesan Di Era Digital - Ilham Rizqi Ariyandi; Plora Pasaribu; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
Innovation has become a key element in business strategies in the digital era, marked by technological advancements and changes in consumer behavior. This study discusses the importance of integrating innovation into business strategies to create sustainable competitive advantages. It also identifies challenges in implementing innovation, such as costs, organizational resistance, and a lack of skilled human resources. Through case studies of companies such as Amazon, Gojek, and Tokopedia, this article provides strategic recommendations, including fostering an innovation culture, investing in technology, and pursuing external collaborations. With well-planned steps, companies can leverage innovation to enhance operational efficiency, expand market share, and effectively meet customer needs.